Predictive factors for persistent thrombocytopenia after peptide receptor radioligand therapy in enteropancreatic neuroendocrine tumors - Ferrara, Romain; Zemmour, Christophe; Reichert, Thibaut; Ouk, Daniel; Niccoli, Patricia; Maniry-Quellier, Jemima; Brenot-Rossi, Isabelle; Charrier, Nathalie; Oziel-Taieb, Sandrine (Frontiers in Endocrinology, 2025)
IntroductionPeptide receptor radionuclide therapy (PRRT) is an effective and well-tolerated treatment for advanced neuroendocrine tumors (NETs). However, persistent thrombocytopenia (PT) has been reported and may compromise further therapies and outcomes. This study aimed to identify predictive factors for PT defined as a platelet count <100 x 109/L, 2 months after the end of PRRT.MethodsWe performed a single-center retrospective analysis of clinical, biological, and imaging parameters of metastatic NET patients undergoing [177Lu]Lu-DOTATATE therapy. Bone metastatic volume was quantitatively measured and converted into an Osteo-Medullary Invasion Score (OMIS). The initial decline of platelet count (IDPC) was defined as the relative change (%) in platelet count between the baseline and the nadir value before the second cycle.ResultsIn total, 47 patients (25 women, 22 men, median age 68 years) were included. Fifteen patients (31.9%) had bone metastases, and five (10.6%) had an OMIS ≥ 30%. Six patients (15.4%) presented with a spleen length ≥ 100 mm. Median follow-up was 50.1 months. Median IDPC was 26%. Eight patients (17%) presented with PT. PT was associated with an OMIS ≥ 30% (p < 0.001; odds ratio not estimable), a spleen length ≥ 100 mm (p = 0.04; odds ratio = 7), and an IDPC ≥ 30% (p= 0.014: odds ratio = 15.8), and was unrelated to age, gender, previous cancer, previous therapies, and cumulative activity.ConclusionWe found that 17% of PT incidence correlated with relatively high bone metastatic burden and spleen length. Physicians should be vigilant in the event of a significant drop in platelet count after the first cycle of PRRT.